Dental Caries and Preventive Dental Visits Among Children in the U.S.: The Impact of Race/Ethnicity and Immigration - Huabin Luo, PhD; Bei Wu, PhD; Yanyan Wu, PhD; Mark E. Moss, DDS, PhD (Elsevier, 2024)
Introduction: National data on dental caries and dental service use among immigrant children in U.S. are limited. It is not known whether race/ethnicity would interact with immigration status to increase these disparities. Using a nationally representative sample, this study assessed the interaction effects of immigrant generation status and race/ethnicity on dental caries and dental visits among children in the U.S. Methods: Data were from the 2020 and 2021 National Survey of Children's Health. All data were self-reported by parents/guardians. The 2 outcomes were (1) dental caries (yes/no) in the past 12 months and (2) preventive dental visits (yes/no) in the past 12 months. Racial/ethnic groups included non-Hispanic White, Black, Hispanics, and Asian Americans. The analytical sample included 66,167 children aged 2-17 years, including 1,243 first-generation immigrant children; 11,017 second-generation immigrant children; and 53,907 nonimmigrant children. Study authors ran separate multiple logistic regression models for the 2 outcome variables. All analyses accounted for the survey design of National Survey of Children's Health. Results: First-generation immigrant children were more likely to have dental caries than nonimmigrant children (AOR=1.44). The interaction of race/ethnicity and immigrant generation status was significant (p=0.04) in the preventive dental visits model, indicating increased challenges in getting dental visits among minority immigrant children in comparison with that among non-Hispanic White immigrant children, especially among first-generation immigrant children of Asian Americans (AOR=0.41) and non-Hispanic Black immigrant children (AOR=0.37). Conclusions: First-generation immigrant children were less likely to see a dentist and more likely to have dental caries than nonimmigrants. Moreover, first-generation immigrant children from minority racial/ethnic groups were the least likely to seek dental services. To further reduce disparities in oral health and dental use among children in the U.S., culturally sensitive health promotion is warranted to improve oral health literacy and reduce barriers to dental care for immigrants, especially immigrant children of the minority groups.